Custom Metal Occlusal Surface for Acrylic Resin Denture Teeth to Enhance Wear Resistance: A Case Report. (10th September 2012) - Shivji, Rizwan Ali; Kamble, Vaibhav D.; Khan, Mohd. Atif
Abstract : Wear of the occlusal surface of the denture is a known fact which leads to subsequent changes in jaw relation, vertical dimension, loss of aesthetics, aged looks, and decrease in masticatory efficiency. Treatment modalities includes, change of denture set after a regular interval of 4-5 years, use of wear resistant denture teeth that includes wear resistant resin or porcelain teeth, teeth with cast metal occlusal surface, and altering occlusal contact areas of denture teeth by use of silver amalgam fillings. A case report of a patient who had increased tendency of occlusal wear was treated with custom made metal occlusal surface of denture teeth to enhance wear resistance and to improve the masticatory efficiency.